2008
DOI: 10.1097/wnr.0b013e3282ffb574
|View full text |Cite
|
Sign up to set email alerts
|

The recovery cycle of bat duration-selective collicular neurons varies with hunting phase

Abstract: During hunting, duration selectivity and recovery cycle underlie a bat's ability to determine echo duration and target distance (echo ranging). This study shows that the recovery cycle of most duration-selective neurons in the bat central nucleus of the inferior colliculus neurons varies with biologically relevant pulse-echo (P-E) duration and amplitude. As such, neurons with short best duration recover rapidly when stimulated with P-E pairs with short duration and small P-E amplitude difference, whereas neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 22 publications
4
29
0
1
Order By: Relevance
“…Sleep and circadian rhythm are known to be disrupted in MPTP-treated rodents (Laloux et al 2008), rotenone-treated rats (García-García et al 2005), and Thy1-αSyn mice and VMAT2-deficient mice (Taylor et al 2009). Gastrointestinal function has been shown to be abnormal in MPTP-treated mice (Anderson et al 2007), rotenone-treated rats (Drolet et al 2009), Thy1-αSyn mice (Wang et al 2008, 2012), SNCA PAC mice (which expresss mutant human α-synuclein from a P1 artificial chromosome containing its endogenous regulatory elements) (Kuo et al 2010), and VMAT2-deficient mice (Taylor et al 2009). These findings are of interest because they demonstrate that toxicant exposures and genetic manipulations used to induce motor signs of PD can also induce non-motor features.…”
Section: Implications For Parkinson’s Etiology and Experimental Researchmentioning
confidence: 99%
“…Sleep and circadian rhythm are known to be disrupted in MPTP-treated rodents (Laloux et al 2008), rotenone-treated rats (García-García et al 2005), and Thy1-αSyn mice and VMAT2-deficient mice (Taylor et al 2009). Gastrointestinal function has been shown to be abnormal in MPTP-treated mice (Anderson et al 2007), rotenone-treated rats (Drolet et al 2009), Thy1-αSyn mice (Wang et al 2008, 2012), SNCA PAC mice (which expresss mutant human α-synuclein from a P1 artificial chromosome containing its endogenous regulatory elements) (Kuo et al 2010), and VMAT2-deficient mice (Taylor et al 2009). These findings are of interest because they demonstrate that toxicant exposures and genetic manipulations used to induce motor signs of PD can also induce non-motor features.…”
Section: Implications For Parkinson’s Etiology and Experimental Researchmentioning
confidence: 99%
“…Proteinase K-resistant α-Syn inclusions also have been identified in many brain regions of these mice (Fernagut et al, 2007; Fleming et al, 2008), and the mice show progressive sensorimotor alterations, beginning as early as 2 months of age (Fleming et al, 2004, 2006). Because the mice have a full complement of nigral dopamine (DA) cell bodies and striatal DA terminals at the times when they exhibit such deficits (Fernagut et al, 2007), it has been proposed that, at these early ages, they represent a model of premanifest PD (Chesselet, 2008), a contention supported by the demonstration of early nonmotor olfactory deficits and autonomic changes in these mice characteristic of early stages of the disease (Fleming et al, 2008; Wang et al, 2008; Magen and Chesselet, 2010). …”
mentioning
confidence: 99%
“…Indeed, we have shown previously that the echo frequency and amplitude sensitivity of duration-sensitive collicular neurons are better for expected than for unexpected echo durations [8,9,25]. We have also shown that collicular neurons with a short best duration recover rapidly when stimulated with P-E pairs with short durations and small P-E amplitude differences, whereas neurons with a long best duration recover rapidly when stimulated with P-E pairs with long durations and large P-E amplitude differences [26]. Furthermore, echo duration and frequency sensitivity of collicular neurons improve with decreasing P-E duration, P-E gap, and P-E amplitude difference [7,9,27].…”
Section: Discussionmentioning
confidence: 68%